First case of bacteraemia due to Acinetobacter schindleri harbouring blaNDM-1 in an immunocompromised patient - S. Montaña; S. Palombarani; M. Carulla; A. Kunst; C.H. Rodriguez; M. Nastro; C. Vay; M.S. Ramirez; M. Almuzara (New Microbes and New Infections, 2018)
Clinically significant NDM-1-producing Acinetobacter schindleri has not yet been described in the literature. We report the first case of bacteraemia due to an A. schindleri strain harbouring blaNDM-1 recovered from an immunocompromised patient. Our report reinforces the fact that NDM-1 can easily be acquired by Acinetobacter species. Keywords: Acinetobacter schindleri, bacteraemia, blaNDM-1, clinically significant isolate, immunocompromised patient